Risk of Helicobacter pylori infection in newborn babies of Helicobacter pylori-positive pregrant woman - Mehmet DURSUN; Vedat GÖRAL; Halis ŞİMŞEK and Vahit YÜKSELEN and Gülşen HASÇELİK and Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2019)
-